2014
DOI: 10.3390/toxins6123296
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis Toxins: An Overview of Their Biocidal Activity

Abstract: Bacillus thuringiensis (Bt) is a Gram positive, spore-forming bacterium that synthesizes parasporal crystalline inclusions containing Cry and Cyt proteins, some of which are toxic against a wide range of insect orders, nematodes and human-cancer cells. These toxins have been successfully used as bioinsecticides against caterpillars, beetles, and flies, including mosquitoes and blackflies. Bt also synthesizes insecticidal proteins during the vegetative growth phase, which are subsequently secreted into the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
509
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 615 publications
(560 citation statements)
references
References 157 publications
5
509
0
19
Order By: Relevance
“…However, when examined, there is a lack of direct correlation between structure and activity against specific targets, i.e. the same Cry toxin can be active against taxonomically diverse insects and Cry toxins with diverse binding determinants (domains II and/or III) may be active against the same insect (Palma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, when examined, there is a lack of direct correlation between structure and activity against specific targets, i.e. the same Cry toxin can be active against taxonomically diverse insects and Cry toxins with diverse binding determinants (domains II and/or III) may be active against the same insect (Palma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Palma et al (2014) reported that 700 Bt cry genes (Cry proteins) have been identified in the past decades. While many Cry proteins have pesticidal properties against insect pests in agriculture, others have no known invertebrate targets and have been termed "parasporins".…”
Section: Nomenclature Of Cry and Cyt Toxins (Proteins)mentioning
confidence: 99%
“…Significant progress has been made in recent years in the elucidation of new toxin structures and the potential to derive reliable structures from modelling approaches is discussed elsewhere in this issue (Berry and Board, 2016). Similarly, while there are a lot of data available on the target specificity of individual toxins (Palma et al, 2014a;van Frankenhuyzen, 2009), many of these are contradictory, thus compounding efforts to derive meaningful associations. The area where least information is known concerns the interaction of the toxin with the target cell (Vachon et al, 2012).…”
Section: The Future For In Silico Analysesmentioning
confidence: 99%
“…Within the 3-domain toxin family, we find toxins with activity against insects in several orders, principally amongst the Lepidoptera with fewer active against the orders Diptera and Coleoptera, and with small numbers active against Hymenoptera and Hemiptera as well as toxins affecting nematodes and gastropods (reviewed recently (Palma et al, 2014a)). …”
mentioning
confidence: 99%